Investment in ICT, Productivity, and Labor Demand: The Case of Argentina - Brambilla, Irene (2018)
This paper explores the impact of the adoption of information and communications technology on firm performance and labor market outcomes using a firm survey from the manufacturing sector in Argentina. The findings are that at the firm level adoption of information and communications technology leads to increases in firm productivity and wages, and that the effects are heterogeneous across firms, being larger for initially high-productivity and high-skill firms. The increase in wages occurs even after controlling for skill composition, implying that there are productivity and rent-sharing mechanisms at play. Further findings show that adoption of information and communications technology is associated with employment turnover as captured by the replacement of workers, elimination of occupations, creation of new occupations, and decrease in the share of unskilled workers, supporting the view that ICT is complementary with skilled labor. At the same time, there is an increase in employment across all skill categories. This result is compatible with positive output effects that drive employment, and with job turnover within the unskilled group.